Problematika Penerapan Prinsip Due Process of Law dalam Hukum Acara Pengujian Undang-Undang di Mahkamah Konstitusi - Ayu Wulandari; Sidi Ahyar Wiraguna (Lembaga Pengembangan Kinerja Dosen, 2025)
The principle of due process of law is a fundamental pillar in every modern legal system, including in the context of procedural law for judicial review of laws at the Constitutional Court of the Republic of Indonesia. This principle demands a fair, open, and balanced procedure for all parties to the case. However, in practice, the application of this principle often faces various problems, such as limited access to trial information, limited opportunities to submit evidence, and allegations of impartiality by the constitutional panel of judges. This study aims to critically examine the problems of applying the principle of due process of law in procedural law for judicial review of laws at the Constitutional Court. The research method used is normative juridical with a statutory approach and case studies of several Constitutional Court decisions. The results of the study indicate that there is a discrepancy between the normative provisions governing the principle of a fair trial and the factual implementation in court. This condition has the potential to weaken the legitimacy of the Constitutional Court as the guardian of the constitution and the protection of citizens' constitutional rights. Therefore, efforts are needed to reform procedural law at the Constitutional Court to strengthen the application of the principle of due process of law consistently, transparently, and accountably.